STRATEGI KEPEMIMPINAN KEPALA DESA UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN INFRASTRUKTUR JALAN DESA - Rahman, Budi; Mulyadi, Edi; Hardian, Dafyar Eliadi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study aims to analyze the village head's leadership strategies in increasing community participation in village road infrastructure development in Binturung Village, North Pamukan District, Kotabaru Regency. The study used a descriptive qualitative approach, with data collection techniques through interviews, observation, and documentation. The results indicate that the village head implemented participatory, communicative, and collaborative leadership strategies, thereby increasing community awareness and involvement in development. Supporting factors in this study included a spirit of mutual cooperation, village government support, and open leadership. Challenges encountered included budget limitations, differing interests, and varying levels of participation among residents. The study concluded that an effective village head leadership strategy can encourage optimal community participation in village infrastructure development, particularly village roads. Keywords: Village Head Leadership, Community Participation, Infrastructure Development, Village Roads.